Diagnosis of nontuberculous respiratory diseases - Narvaez O., Víctor (1956)
Until about two decades ago, the first diagnosis for bronchopulmonary disorders extended evolution was usually tuberculosis, then a long list of non-tuberculous respiratory conditions considered in the differential diagnosis. Currently, non-tuberculous disease has increased with the increasing incidence of lung cancer, as well as the increase in cases of pneumoconiosis caused by inhalation of harmful substances used in modern industries.